ESIPT-Based Photoactivatable Fluorescent Probe for Ratiometric Spatiotemporal Bioimaging - Xiaohong Zhou; Yuren Jiang; Xiongjie Zhao; Dong Guo (Sensors, 2016)
Photoactivatable fluorophores have become an important technique for the high spatiotemporal resolution of biological imaging. Here, we developed a novel photoactivatable probe (PHBT), which is based on 2-(2-hydroxyphenyl)benzothiazole (HBT), a small organic fluorophore known for its classic luminescence mechanism through excited-state intramolecular proton transfer (ESIPT) with the keto form and the enol form. After photocleavage, PHBT released a ratiometric fluorophore HBT, which showed dual emission bands with more than 73-fold fluorescence enhancement at 512 nm in buffer and more than 69-fold enhancement at 452 nm in bovine serum. The probe displayed a high ratiometric imaging resolution and is believed to have a wide application in biological imaging.